Microalbuminuria among Newly Diagnosed Diabetic Patients at Mulago National Referral Hospital in Uganda: A Cross Sectional Study - Martin, Muddu (J Obes Weight Loss Medicat, 2018)
BACKGROUND: Microalbuminuria is an early marker of nephropathy, cardiovascular diseases and severe ocular morbidity in adults with diabetes mellitus. This subclinical condition is associated with high morbidity and mortality. Microalbuminuria precedes the development of overt diabetic nephropathy by 10–14 years. At this stage, one can reverse diabetic nephropathy or prevent its progression. Unfortunately, tests to detect microalbuminuria in diabetics are not routinely done in Uganda. This study sought to determine the prevalence and factors associated with microalbuminuria among newly diagnosed diabetic patients in the National Referral Hospital in Uganda. METHODS: In this cross-sectional study conducted between June 2014 and January 2015, we recruited 175 newly diagnosed adult diabetic patients. Information on patients’ socio-demographics, biophysical profile, blood pressure measurement, biochemical testing and echocardiographic findings was obtained for all the participants using a pre-tested questionnaire. Microalbuminuria was defined as Albumin to Creatinine Ratio (ACR) between 30 and 299 mg/g. Bivariate and multivariate logistic regression analyses were used to investigate the association of several factors with microalbuminuria. RESULTS: Of the 175 patients recruited, males were 90 (51.4%) and the mean age was 46 ± 15 years. Majority of patients had type 2 DM 140 (80.0%) and the rest had type 1 DM 35 (20.0%). The mean HbA1C was 13.9 ± 5.3%. Mean duration of diabetes was 2 months. Prevalence of microalbuminuria was 47.4% (95% CI: 40.0%−54.9%) among all the patients that were assessed in the study. The independent factor associated with microalbuminuria was pregnancy (OR7.74[95% CI: 1.01–76.47] P = 0.050) while mild and moderate physical activity at work were inversely associated with microalbuminuria respectively (OR0.08[95% CI: 0.01–0.95] P = 0.046) and (OR0.07[95% CI: 0.01–0.77] P = 0.030). CONCLUSIONS: Prevalence of microalbuminuria was high in this patient population of newly diagnosed diabetes mellitus. Pregnancy was positively associated with significant microalbuminuria while physical activity at work was inversely associated with microalbuminuria. Early detection and management of microalbuminuria in asymptomatic individuals may help in preventing deterioration in renal function and development of overt diabetic nephropathy and progression to ESRD.